LC3A-mediated autophagy regulates lung cancer cell plasticity. Issue 4 (3rd April 2022) - Miao, Chia-Cheng; Hwang, Wen; Chu, Ling-Yi; Yang, Li-Hao; Ha, Cam-Thu; Chen, Pei-Yu; Kuo, Ming-Han; Lin, Sheng-Chieh; Yang, Ya-Yu; Chuang, Shuang-En; Yu, Chia-Cherng; Pan, Shien-Tung; et al.
ABSTRACT: Cancer cell plasticity generates heterogeneous oncogenic subpopulations in tumors. How macroautophagy/autophagy, a catabolic system required for sustaining cell homeostasis, affects cancer cell plasticity, remains elusive. In this study, we report that MAP1LC3A/LC3A (microtubule associated protein 1 light chain 3 alpha), a key molecule in autophagy, is negatively associated with histological grade and distant metastasis of lung cancer. This is achieved in part, if not all, by maintaining the mitochondria and energy homeostasis to meet the proliferation demand of lung cancer cells driven by SOX2 (SRY-box transcription factor 2) signaling. Basal autophagy is preferentially active in SOX2-positive lung cancer cells with high-proliferative and low-invasive properties. The high-proliferative cancer cells exhibit higher oxygen consumption rate (OCR), elevated reactive oxygen species (ROS), and profound fragmented mitochondrial patterns compared to their high-invasive counterparts. SOX2 expression promotes LC3A expression and enhances proliferation but attenuates invasion in lung cancer cells. LC3A silencing enriches cells harboring low-proliferative and high-invasive features, concomitant with decreased OCR and ROS levels and reduced expression of SOX2 . Our findings provide novel insights into how basal autophagy cross talks with SOX2 proliferation signaling to regulate mitochondrial metabolism and determines cancer cell plasticity with an impact on lung tumor progression. Abbreviations: ATG14: autophagy related 14; CDH2: cadherin 2; ChIP-qPCR: chromatin immunoprecipitation quantitative polymerase chain reaction; CQ: chloroquine; ECAR: extracellular acidification rate; EMT: epithelial-mesenchymal transition; EPCAM: epithelial cell adhesion molecule; MAP1LC3A/LC3A: microtubule associated protein 1 light chain 3 alpha; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MAP1LC3C/LC3C: microtubule associated protein 1 light chain 3 gamma; NDUFV2: NADH:ubiquinone oxidoreductase core subunit V2; OCR: oxygen consumption rate; ROS: reactive oxygen species; RT-qPCR: reverse-transcriptase quantitative polymerase chain reaction; SC: scrambled control; sh RNA : short hairpin RNA; SNAI2: snail family transcriptional repressor 2; SOX2: SRY-box transcription factor 2; SQSTM1/p62: sequestosome 1; TGFB/TGF-β: transforming growth factor beta; TOMM20: translocase of outer mitochondrial membrane 20; ZEB1: zinc finger E-box binding homeobox 1